Neuroimaging reveals functionally distinct neuronal networks associated with high-level alcohol consumption in two genetic rat models - Pallares, Vicente; Dudek, Mateusz; Moreno, Andrea; Pérez-Ramírez, Úrsula; Moratal, David; Haaranen, Mia; Ciccocioppo, Roberto; Sommer, Wolfgang H.; Canals, Santiago; Hyytiä, Petri (Behavioural pharmacology, 2021)
Human imaging data suggest that the motivational processes associated with alcohol reward are reflected in the patterns of neural activation after alcohol or alcohol-related cues. In animal models of alcohol drinking, however, the changes in brain activation during voluntary alcohol ingestion are poorly known. In order to improve the translational utility of animal models, we examined alcohol-induced functional brain activation in Alko Alcohol (AA) and Marchigian-Sardinian alcohol-preferring (msP) rats that drink voluntarily high levels of alcohol, but exhibit widely different neurochemical and behavioral traits cosegregated with alcohol preference. Brain imaging was performed using manganese-enhanced MRI (MEMRI), which is based on accumulation of Mn2+ ions in activated neurons, allowing the identification of functional neuronal networks recruited during specific behaviors in awake animals during a subsequent imaging session under anesthesia. MEMRI was performed following 4 weeks of voluntary alcohol drinking, using water drinking as the control. Despite similar levels of alcohol drinking, strikingly different alcohol-induced neuronal activity patterns were observed in AA and msP rats. Overall, functional activation in the AA rats was more widespread, involving large cortical areas and subcortical structures, such as the bed nucleus of the stria terminalis, preoptic area, hypothalamus, periaqueductal grey, and substantia nigra. In the msP rats, however, alcohol-related activation was largely confined to prefrontal cortical regions and insular cortex, and olfactory areas. Overlapping areas of activation found in both rat lines included the nucleus accumbens, prelimbic, orbital, and insular cortex. In conclusion, our data reveal strikingly different brain circuits associated with alcohol drinking in two genetically different rat lines and suggest innately different motivational and behavioral processes driving alcohol drinking. These findings have important implications for the use of these lines in translational alcohol research.